Animation project stranger danger: the merging of an animation character in live action footage / Mohd Akwa Mohd Arifin - Mohd Arifin, Mohd Akwa (Faculty of Film, Theatre and Animation, 2015)
This thesis discusses the importance of making a visual interaction between an animation character with a real world environment or a real life person. The aim for this research was to study on how the camera movement and the interaction of the animation character with the real world object that affects the presence of the animation character in the live action world. I have gathered the information based on several researches from the same field in order to strengthen my research. Until this very day, there are not many researches that have carried out that specify to this type of topic. However, it has a lot of things which are related to this research. I was referring to the work of Robert Zemeckis in most of my writings. Robert Zemeckis is the director of “Who Framed Roger Rabbit”, which is one of the breakthrough film, known to making history with its hybrid live action animation traits embedded in it. In this research, I have discussed about the ways and techniques to make a hybrid live action animation film. Most of the techniques explained, I did applied it in my final project. By conducting the research on how to make a proper live action animation film, it made the process of making my project easier and tremendously helpful in organizing and planning it. It has been directly improving the quality of my animation project. This study reveals that making the camera move in the live action shots, giving depth and perspective to the animation character while making static camera shots make the animation character looks flat. When the animation character interacts with a real object, it gives a sense of life to the animation character. This is dissimilar when it interacts with a cartoon object, as both belong to the same world.